Catalyst‐Dependent Chemoselective Formal Insertion of Diazo Compounds into C−C or C−H Bonds of 1, 3‐Dicarbonyl Compounds. Issue 29 (8th May 2018) - Liu, Zhaohong; Sivaguru, Paramasivam; Zanoni, Giuseppe; Anderson, Edward A.; Bi, Xihe
Abstract: A catalyst‐dependent chemoselective one‐carbon insertion of diazo compounds into the C−C or C−H bonds of 1, 3‐dicarbonyl species is reported. In the presence of silver(I) triflate, diazo insertion into the C(=O)−C bond of the 1, 3‐dicarbonyl substrate leads to a 1, 4‐dicarbonyl product containing an all‐carbon α‐quaternary center. This reaction constitutes the first example of an insertion of diazo‐derived carbenoids into acyclic C−C bonds. When instead scandium(III) triflate was applied as the catalyst, the reaction pathway switched to formal C−H insertion, affording 2‐alkylated 1, 3‐dicarbonyl products. Different reaction pathways are proposed to account for this powerful catalyst‐dependent chemoselectivity. Abstract : Catalyst control : The catalyst‐dependent chemoselective insertion of diazo compounds into 1, 3‐dicarbonyl species is reported. In the presence of AgOTf, the diazo compounds selectively insert into the C(=O)−C bond, affording 1, 4‐dicarbonyl products with an all‐carbon α‐quaternary center. In contrast, in the presence of Sc(OTf)3, C−H insertion results in α‐C−H alkylation products. The cover picture for this article is presented on the back cover ofAngewandte Chemie issue 32/2018.